Building a Politics of Connectivity: Intercultural In‐Commonness in Fairtrade. Issue 5 (27th April 2020) - Herman, Agatha
Abstract: Fairtrade operates its global system through a homogenising but marketable set of standards. Combined with issues around how to include producers in governance, this has led to feelings of disconnection and disenfranchisement for the latter, which are impacting on Fairtrade's effectiveness and legitimacy. Through a focus on the South African wine industry, this paper argues that the Fairtrade community needs to be reinvigorated through dialogical communication, impactful participation and cultural synthesis to better enact responsibility across its systemic geographical and cultural distances. "Being‐with" its multiple stakeholders makes space for a more responsive, contextual and connected system. Drawing on the ideas of Paulo Freire, the paper concludes that a Fairtrade built on solidarity through a participatory and decentralised system would allow for discussions of the ideals and practices that are essential to negotiating, and not swallowing up, the shifting "we" of Fairtrade and more effectively balancing its local and global responsibilities.